Readiness the Soul Cadres in the Handling of Violence Behavior when the Release of Pasung in Kokop Bangkalan: Menyiapkan Kader Jiwa dalam Penanganan Perilaku Kekerasan saat Pelepasan Pasung di Kokop Bangkalan - Suhron, Muhammad; Yusuf, Ah (Yayasan Ahmar Cendekia Indonesia, 2021)
People with mental disorders (ODGJ) after pasung are defined as ODGJ who have been freed from confinement and referred to the hospital. One way of handling (ODGJ) is post pasung by involving mental cadres in handling violent behavior in people with mental disorders (ODGJ) after pasung. The purpose of this Community Service is to prepare soul cadres in handling violent behavior during the release of pasung. This community service was carried out in November 2019 with the target of soul cadres in Bangkalan Kokop. The team came from the Nursing Study Program at Stikes Ngudia Husada Madura, and the Faculty of Nursing, Airlangga University and the Kokop Community Health Center. This activity consists of a preparatory stage including an assessment / assessment and techniques for handling violent behavior by mental cadres in releasing pasung patients. Abstrak: Orang dengan gangguan jiwa (ODGJ) pasca pasung diartikan ODGJ yang sudah terbebas dari pemasungan dan dirujuk ke rumah sakit, Salah satu cara penanganan (ODGJ) pasca pasung dengan melibatkan Kader jiwa dalam menangani perilaku kekerasan pada Orang dengan gangguan jiwa (ODGJ) pasca pasung. Tujuan Pengabdian Masyarakat ini yaitu untuk menyiapkan kader jiwa dalam penanganan perilaku kekerasan saat pelepasan pasung. Pengabdian masyarakat ini dilakukan pada bulan November 2019 dengan sasaran kader jiwa di Kokop Bangkalan. Tim berasal dari Program Studi Keperawatan Stikes Ngudia Husada Madura, dan Fakultas Keperawatan, Universitas Airlangga serta puskesmas Kokop. Kegiatan ini terdiri dari tahap persiapan meliputi pengkajian/assesment dan tekhnik penanganan perilaku kekerasan oleh kader jiwa dalam pelepasan pasien pasung.